Air mycopopulations in Petrovská klobása producing facility - Škrinjar Marija M.; Petrović Ljiljana S.; Blagojev Nevena T.; Šošo Vladislava M. (Zbornik Matice Srpske za Prirodne Nauke, 2011)
Different types of filamentous fungi periodically cause problems in small-scale facilities for traditional dry fermented sausages, such as Petrovská klobása from Vojvodina province (Serbia). Mould contamination can be observed during processing, ripening, and storage. Sausages may become spoiled due to visible mould colonies on the surface and off-flavours they produce. The most important - if mycotoxin production occurs it might promote a number of health disorders. Knowledge and control of filamentous fungi are, therefore, essential to produce sausages that satisfy the criteria of hygienic quality, sensorial characteristics, and food safety. The aim of this study was to survey mycoflora of a small-scale facility producing traditional dry fermented sausage - Petrovská klobása. The mould contamination of the air in processing unit and ripening chambers was investigated, in order to determine the important fungi in terms of spoilage of the products and ability to produce mycotoxins. The mould contamination of air in processing unit and ripening chambers examined was in range 0.22 - 1.89 log CFU/P.d. Isolated moulds belong to 6 genera: Aspergillus (3 species), Cladosporium (1 species), Eurotium (2 species), Fusarium (1 species), Penicillium (12 species) and Scopulariopsis (1 species). The most abundant were species of Penicillium genus, many of which are capable for mycotoxin production. The level and diversity of fungal contamination of air varied between samples, influenced by the general hygiene, the buildings, the airflow, the outdoor environments, and the time of year. This knowledge is crucial for the improvement of hygiene control systems in small-scale processing units.